Parenting Career and Non-Career Parents in The Internalization of Islamic Educational Values Case Study in Karang Anyar Village, Pegajahan Serdang Bedagai Regency - sintiya, Sindy Sintiya Sindy; Darmayanti, Nefi Darmayanti Nefi; Daulay, Nurussakinah Daulay Nurussakinah (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This study aims to describe the Parenting Style of Career and Non-Career Parents in the Inculcation of Islamic Education Values. Karang Anyar, Pegajahan District, Serdang Bedagai Regency. This research includes descriptive qualitative, in collecting data, researchers used observation, interviews and documentation. For the analysis, the researcher used a qualitative descriptive analysis technique in the form of written or oral data from the interviewees. The validity of the data was checked by the triangulation procedure. The results of the study stated that, most parents in Karang Anyar Village, Pegajahan District, Serdang Bedagai Regency 1) educate their own children at home; 2) go to TPQ/madrasah, for busy parents they send their children to full day school; 3) giving stories of examples of prophets; 4) invite stories of what was experienced; 5) exemplify and make it a habit, for example inviting to the mosque, practicing fasting, praying five times a day, and noble character. Positive impact: children become disciplined and organized, because parents emphasize what they have to do, although parents also give freedom to their children. Religious education from parents and also from TPQ is a strong foundation for the lives of these children. 3) giving stories of examples of prophets; 4) invite stories of what was experienced; 5) exemplify and make it a habit, for example inviting to the mosque, practicing fasting, praying five times a day, and noble character. Positive impact: children become disciplined and organized, because parents emphasize what they have to do, although parents also give freedom to their children. Religious education from parents and also from TPQ is a strong foundation for the lives of these children. 3) giving stories of examples of prophets; 4) invite stories of what was experienced; 5) exemplify and make it a habit, for example inviting to the mosque, practicing fasting, praying five times a day, and noble character. Positive impact: children become disciplined and organized, because parents emphasize what they have to do, although parents also give freedom to their children. Religious education from parents and also from TPQ is a strong foundation for the lives of these children. although parents also give freedom to their children. Religious education from parents and also from TPQ is a strong foundation for the lives of these children. although parents also give freedom to their children. Religious education from parents and also from TPQ is a strong foundation for the lives of these children.